Quality assessment and impact of aquatic environment of higueras river in the province of Huánuco - 2014 - Jacha Ayala, Zocimo P. (2017)
Natural surface water is one of the most widespread, abundant substances on Earth. It is an integralpart of most living things and is present in allowable amount. The naturally pure drinking water isessential for life; the great civilizations have flourished near adequate supplies of the liquid of life.Riparian vegetation plays Higueras river habitat and ecosystem functions. Influences on hydrology,soil science, physicochemical, chemical and microbiological water, so it is relevant in productivity andperformance, regulates temperature, filtering, retaining nutrients and providing habitat for aquatic communities. The study made some approaches on quality and perceived negative impact on waterquality conditions by measuring various physical, chemical and microbiological parameters. Gradientas described sampling stations throughout the course of the channels. The results indicate highpollution and high negative impacts, with the highest incidence in sites close proximity to coastalsettlements channels. The variables which show excessively high values such sites are the accountof bacteria, coliforms and detergent concentrations, physico-chemical parameters. The temporarynature of the water increases the severity of concentration of some contaminants. It is also remarkablethe impact of the deterioration of the natural quality of the physical environment all the way fromsurface waters of the river, mainly due to agricultural activities, extraction of construction materialsand domestic wastewater discharges affecting the biota aquatic. The results indicate that since thewater stations up even still have low impact on quality, while at stations downstream (Season 4, 5, 6,7, 8, 9, 10) are at high risk for contamination, which is confirms strong electric conductivity, turbidity,eutrophication and disappearance of aquatic life becoming to be a dead river, organoleptic, physicalchemical parameters, microbiological very high concentrations and the presence of ammonia andmineral salts that characterize hard water inadmissible for loved alive and human consumption.